Evaluation of chemicals of environmental concern in crumb rubber and water leachates from several types of synthetic turf football pitches. (May 2021) - Celeiro, Maria; Armada, Daniel; Ratola, Nuno; Dagnac, Thierry; de Boer, Jacob; Llompart, Maria
Abstract: Nowadays concern exists about the safety for both football players and the environment of recycled tire rubber used as infill in synthetic turf football pitches. In this study 40 target compounds, including polycyclic aromatic hydrocarbons (PAHs), plasticizers, antioxidants and vulcanization agents were determined in 50 synthetic football pitches of diverse characteristics to estimate environmental risks. This is the first study of crumb rubber sport facilities in Portugal. Analyses were performed by ultrasound-assisted extraction followed by gas chromatography-tandem mass spectrometry (UAE-GC-MS/MS). To evaluate the transfer of the target chemicals from the crumb rubber to the runoff water, water leachates collected from several football pitches were analyzed by solid-phase microextraction (SPME-GC-MS/MS). In addition, lab-scale runoff simulation experiments were performed to assess whether a persistent inflow of the target compounds from the football pitches into the runoff water wcould exist. Results revealed the presence of most of the target PAHs in crumb rubber at total concentrations up to 57 μg g −1, next to a high number of plasticizers and vulcanization agents. Runoff water collected from the football pitches contained up to 13 PAHs as well as other chemicals of environmental concern. In addition, continuous leaching of chemicals from the crumb rubber to the surrounding water was demonstrated. The transfer of target chemicals into the runoff water poses a potential risk for the aquatic environment. Graphical abstract: Image 1 Highlights: The presence of 40 hazardous chemicals was evaluated in Portuguese pitches. Runoff water was analyzed to assess if an inflow of the target compounds exists. Results revealed the presence of PAHs in crumb rubber at concentrations of 57 μg g −1 . Continuous chemicals leaching from crumb rubber to the runoff water was demonstrated. The transfer of chemicals into runoff water poses a risk for the aquatic environment.